Risk behaviors and sexually transmitted infections in women of childbearing age - Malca Herrera, Evelyn L. (2021)
Objective: To assess risk behaviours and sexually transmitted infections in women of childbearing age in two primary care facilities in Tacna, Peru. Material and methods: Non-experimental, cross-sectional study of 177 women of childbearing age attended at La Esperanza and San Francisco health centers, randomly selected to whom a questionnaire to measure sexually transmitted infections developed by the Ministry of Health (MINSA) of Peru was applied, with informed consent. Comparative tables are presented, the Chi-squared statistic was used for the analysis. Results: They are risk behaviors to get sexually transmitted infections, the number of sexual partners, have intercourse with a partner who has had several sexual partners (p<0.05). Of the total number of women of childbearing age with vaginal discharge syndrome (48.59 %), 64.29 % belong to the San Francisco Health Center and 34.41 % to La Esperanza Health Center. A significant difference was found between the risk behaviors of women in both health centers (p<0.05). Conclusion: Risk behaviours and sexually transmitted infections in women of childbearing age in two primary care facilities in Tacna are different.